(untitled) (World Bulletin of Social Sciences, 2021)
The article describes the measures aimed at studying and eliminating negative factors that affect the health of employees in the glass production enterprise located in Kuvasoy city of Fergana region. The results of the study showed that the concentration of dust, vapor, gas, aerosols from chemicals in the air of the working area is higher than all workplaces at the enterprise. In the hot period of the year, the microclimate indicators in the workplace did not meet the hygienic requirements, and the content of dolomite and quartz dust, nitrogen oxides, carbon and sulfur in the emissions of atmospheric air was higher than normal. These conditions have a negative impact on the health of employees, leading to stress in the thermoregulatory process and changes in the functional state of the cardiovascular system.